Unraveling athletic performance: Transcriptomics and external load monitoring in handball competition - Condeminas, P. E.; Mallol, M.; Font, R.; Tremps, V.; Gutiérrez, J. A.; Rodas, G.; Lluna, A. P.; Soria, J. M. (PLOS ONE, 2024)
Objective This study aims to comprehend the impact of handball practice on sub-elite athletes by investigating transcriptomic changes that occur during a match. The primary focus encompasses a dual objective: firstly, to identify and characterize these transcriptomic alterations, and secondly, to establish correlations between internal factors (gene expression), and external loads measured through Electronic Performance and Tracking Systems (EPTS variables). Ultimately, this comprehensive analysis seeks to evaluate both acute and chronic responses to exercise within the context of handball training.